Substitution reactions in the acenaphthene analog of quino[7,8-h]quinoline and an unusual synthesis of the corresponding acenaphthylenes by tele-elimination - Kolupaeva, Ekaterina V.; Dzhangiryan, Narek A.; Pozharskii, Alexander F.; Demidov, Oleg P.; Ozeryanskii, Valery A. (Beilstein Journal of Organic Chemistry, 2024)
The possibility of functionalization of dipyrido[3,2-e:2′,3′-h]acenaphthene containing a quino[7,8-h]quinoline fragment and being a highly basic diazine analog of 1,8-bis(dimethylamino)naphthalene (“proton sponge”) has been studied for the first time. In addition to the pronounced tendency of the title compound to form associates with an intramolecular hydrogen bond of the NHN type (new examples with the participation of pyridine rings, including self-associates are shown) and its inertness to amination reactions of the pyridine rings, the naphthalene core at positions 5(8) and the CH2CH2 bridge (dehydrogenation) undergo chemical modifications under mild conditions, giving the corresponding acenaphthylenes. The latter can also be obtained in an unusual way by tele-elimination from 5,8-dibromodipyridoacenaphthene by reaction with neutral or anionic bases.
Keywords: dipyrido[3,2-e:2′,3′-h]acenaphthene (acenaphthylene); hydrogen bonding; π-stacking; substitution reactions; tele-elimination